Exploring the genetic variability in water use efficiency: Evaluation of inter and intra cultivar genetic diversity in grapevines - Tortosa, Ignacio; Escalona, José Mariano; Bota, Josefina; Tomás, Magdalena; Hernández, Esther; Escudero, Enrique García; Medrano, Hipólito (Plant science (Limerick), 2016)
•The WUEi can be used as selection criteria to improve WUE in grapevines.•There is a wide variability of the WUEi among grapevine cultivars.•Inside clones of Tempranillo the WUEi variability is around 80% than among cultivars.•Some cultivars and clones with higher and lower WUEi than the average were identified. Genetic improvement of crop Water Use Efficiency (WUE) is a general goal because the increasing water scarcity and the trend to a more sustainable agriculture. For grapevines, this subject is relevant and need an urgent response because their wide distribution in semi-arid areas. New cultivars are difficult to introduce in viticulture due to the narrow dependency of consumer appreciation often linked to a certain particular wine taste. Clones of reputed cultivars would presumably be more accepted but little is known on the intra-cultivar genetic variability of the WUE. The present work compares, on the basis of two field assays, the variability of intrinsic water use efficiency (WUEi) in a large collection of cultivars in contrast with a collection of clones of Tempranillo cultivar. The results show that clonal variability of WUEi was around 80% of the inter-cultivar, thus providing a first assessment on the opportunity for clonal selection by WUE. Plotting the WUEi data against stem water potential or stomatal conductance it was possible to identify cultivars and clones out of the confidence intervals of this linear regression thus with significantly higher and lower WUEi values. The present results contribute to open the expectative for a genetic improvement of grapevine WUE